Implementasi Sistem Pemesanan Hotel Menggunakan Algoritma Haversine untuk Optimalisasi Rekomendasi Lokasi - Adhani, Hamka Lukmanul Hakim; Bianto, Mufti Ari; Pratama, Alif Nanda; Hidayah, Septina Alfiani (Jurnal Informatika Terpadu, 2025)
A location-based lodging recommendation system helps users find nearby hotels efficiently through a web-based platform. The system utilizes the Haversine algorithm to calculate the distance between the user's location and the hotel by automatically retrieving coordinates via the Geolocation API. Calculated distances are compared with hotel data stored in a MySQL database, and the results are displayed on a web interface integrated with the Google Maps API. Testing was conducted on six hotels with distances ranging from 6.73 km to 23.97 km, and results were compared with Google Maps estimates. The system achieved an average distance difference of 0.0183 km, with an accuracy rate of 99.83%. These findings indicate that the Haversine algorithm provides highly accurate distance estimations and is reliable for location-based hotel recommendation systems.